ASSESSMENT OF PHYSICAL HEALTH OF SCHOOLS GRADUATES GOING TO THE UNIVERSITIES - V. M. Klimov; R. I. Aizman (Бюллетень сибирской медицины, 2016)
Aim. The complex assessment of the level of physical health of schools graduates is presented in the article.Materials and methods. We studied the condition of the first-year students who were assigned to the main medical group. Their physical and psychofunctional condition was estimated using morphological, functional, psychophysiological parameters and the indicators of physical preparedness.Results. Morfofunctional level of the health of the youths who entered higher educational institution was at the average level according to the age-sex norms. At the same time physical preparedness of young men and girls corresponded to satisfactory level, but endurance, the major physical parameter reflecting the general level of working capasity of the person, was below an average. The psychophysiological status of the majority of surveyed was characterized by the optimum force and mobility of nervous processes, good level of social and psychological adaptation, resistance to stress, semantic and image memory. The indicator of anxiety was significantly lower and resistance to stress and adaptation higher in young men than those in girls.